2013
DOI: 10.1111/jam.12197
|View full text |Cite
|
Sign up to set email alerts
|

Zinc as an agent for the prevention of biofilm formation by pathogenic bacteria

Abstract: Aims: Biofilm formation is important for the persistence of bacteria in hostile environments. Bacteria in a biofilm are usually more resistant to antibiotics and disinfectants than planktonic bacteria. Our laboratory previously reported that low concentrations of zinc inhibit biofilm formation of Actinobacillus pleuropneumoniae. The aim of this study is to evaluate the effect of zinc on growth and biofilm formation of other bacterial swine pathogens. Methods and Results: To determine the effect of zinc on biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 42 publications
5
58
1
Order By: Relevance
“…Interestingly, evidence shows the importance of zinc for surface protein interactions that contribute to aggregation and biofilm formation of Staphylococcus aureus , another significant human pathogen (Conrady et al, 2008; Formosa-Dague et al, 2016). However, in contrast, high concentrations of zinc have also been shown to inhibit biofilm formation in the Gram-positive organism Streptococcus suis (Wu et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, evidence shows the importance of zinc for surface protein interactions that contribute to aggregation and biofilm formation of Staphylococcus aureus , another significant human pathogen (Conrady et al, 2008; Formosa-Dague et al, 2016). However, in contrast, high concentrations of zinc have also been shown to inhibit biofilm formation in the Gram-positive organism Streptococcus suis (Wu et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the ability of DznuA to acquire Zn 2+ by the ABC transporter, and through other processes, such as peptide uptake and degradation in vivo. In addition, there is some evidence that zinc inhibits biofilm formation by many respiratory pathogens, such as A. pleuropneumoniae (Wu et al, 2013). However, it remains to be confirmed that the attenuation * This pig was not challenged and was euthanised at the same time as the other surviving pigs for use as a negative control.…”
Section: Discussionmentioning
confidence: 97%
“…The assay of biofilm formation in microtiter plates was adapted from the work of Wu et al (16) and is sum- 1. Briefly, colonies of E. coli on LB agar were resuspended in 5 ml of fresh LB and were incubated at 37°C with shaking (180 rpm) for 16 h. These cultures were then diluted (1:100) in 5 ml of M9 medium with glucose (0.4%, wt/vol) and were incubated at 37°C with shaking (180 rpm) for 24 h. A 1-ml volume was transferred to a 1.5-ml Eppendorf tube, and the bacteria were collected by centrifugation (14,000 ϫ g, 2 min).…”
Section: Methodsmentioning
confidence: 99%